Literasi Media Sosial Di Era Post Truth - Regina Anggi Garbani; Rieka Yulita Widaswara; I Gede Bayu Wijaya (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2021)
Social media is one of the new media which in addition to having a positive impact as technological advancement. The ease and speed of interacting and disseminating information is the main attraction of this service. In addition to having a positive impact, social media also has a negative impact as a medium for disseminating information. The negative side of technological progress through social media creates a new phenomenon in the midst of this digital era called post-truth. Post-truth as a new era is marked by the exclusion of truth and putting forward emotions. In simple terms, post-truth can be interpreted that people are looking for justification rather than the truth. This paper aims to find out how social media literacy is in the post-truth era. Social media literacy is a person's skill in finding, selecting, and applying information sources on social media. These skills are needed to remain able to carry out social media activities wisely and safely so that audiences are critical of the media as well as determine the information needed from the media. In addition, the government's efforts through the regulation of the ITE Law are an important way to combat post-truth on social media.